Charge Syndrome - Tanveer Chaudhry, Mumtaz Hussain, Irfan Qayyum, Muhammad Moin (Pakistan Journal of Ophthalmology, 2008)
A 2 yrs old female born at term presented to us with poor vision, inability to close her eyes since birth and enucleation of left eye at 1 month of age. On examination left orbit and socket were shrunken after enucleation. There was bilateral lid coloboma on medial half with symblephron and ankyloblephron formation. Extra ocular movements were reduced due to conjunctival and corneal adhesion to the upper lid. There was right corneal opacity due to ankyloblephron and limbal vascularization along with exposure keratopathy, associated with conjunctival congestion. There was right lower lid ectropion. There was no uveal coloboma; lens was clear with good fundal glow. She had multiple other congenital anomalies associated with CHARGE syndrome.